Quick Guide Crypto Assets How they Classify within the Framework of Financial Market Law - Appel, Hannah (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2023)
In this book, the complex topic of crypto securities is presented in a compact, understandable and practical manner. In addition to conveying the fundamentals and technical background of the crypto market, a classification in the various areas of regulatory law is made. The focus is on German law, although reference is also made to the European equivalence standards. In order to succeed in a correct classification into European financial market law, both the Liechtenstein law on tokens and VT service providers and the European proposal for a regulation on markets for crypto assets are discussed in detail and compared with the German regulatory provisions on crypto assets. The goal, in addition to creating a basic understanding of how crypto assets work, is to construct a comprehensive overall picture of their regulatory treatment in Germany and to include possible implications of a European push. The work thus provides guidance for individuals who, for example, want to invest in crypto assets or start a business related to crypto assets. The Contents: - Basic knowledge of crypto assets - Regulatory classification of crypto assets - Developments on national and European level (TVTG, MiCAR) - Comparison and critical appraisal of regulatory approaches. The Author: Hannah Appel is a staff member of the Research Lab for Law and applied Technologies at Frankfurt University of Applied Sciences and an associate at a leading international commercial law firm. Already during her studies of business law, she intensively dealt with digitalization topics as well as European and financial market law. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. .
Basic knowledge of crypto assets -- Regulatory classification of crypto assets -- Developments at national and European level -- Comparison and critical appraisal of regulatory approaches.
Keywords: Finance; Capital market; Financial Economics; Capital Markets